2010
DOI: 10.1002/app.31685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and penetration depth on photopolymerization of n‐butyl acrylate using a narrow channel reactor

Abstract: The influence of temperature and reactor size on photopolymerization kinetics of n-butyl acrylate (n-BA) using narrow channel reactors has been investigated. Experimental results have shown that increase in temperature and decrease in size of the reactor increases the monomer conversion. The effect of temperature was studied by immersing the reactor in a water bath maintained at different temperatures. A narrow channel glass reactor, 900 mm long, with diameters 1.5 mm, 1.0 mm, and 0.5 mm respectively were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A follow-up paper investigated the effect of the channel diameter (from 1.5 to 0.5 mm) and demonstrated that a more uniform irradiation was obtained in the narrow diameter reactor. 385 This resulted in a higher conversion (∼15% more in flow within 9.5 s) and lower polymer branching (0.42% molar branching at 30 °C by keeping the temperature constant, 1.334% molar branching without control over the temperature). Efficient light distribution within the reactor vessel becomes increasingly important when scattering effects are more pronounced.…”
Section: Polymer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A follow-up paper investigated the effect of the channel diameter (from 1.5 to 0.5 mm) and demonstrated that a more uniform irradiation was obtained in the narrow diameter reactor. 385 This resulted in a higher conversion (∼15% more in flow within 9.5 s) and lower polymer branching (0.42% molar branching at 30 °C by keeping the temperature constant, 1.334% molar branching without control over the temperature). Efficient light distribution within the reactor vessel becomes increasingly important when scattering effects are more pronounced.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Moreover, lower PDI was observed in the microreactor compared to batch (2.03 vs 9.61). A follow-up paper investigated the effect of the channel diameter (from 1.5 to 0.5 mm) and demonstrated that a more uniform irradiation was obtained in the narrow diameter reactor . This resulted in a higher conversion (∼15% more in flow within 9.5 s) and lower polymer branching (0.42% molar branching at 30 °C by keeping the temperature constant, 1.334% molar branching without control over the temperature).…”
Section: Continuous-flow Photochemistry In Materials Sciencementioning
confidence: 99%
“…Such immersion‐type photochemical reactor is one of the most common reactor configuration used at laboratory scale, and has been commonly involved in many photolysis (water purification), photocatalysis, and photoinduced organic reactions . However, there have been fewer examples of polymerizations performed in this vessel or even in other photochemical reactors . As displayed in Figure , the lamp in this photoreactor is centered parallel to the axis of the reactor vessel and separated from the miniemulsion by a cooling tube.…”
Section: Resultsmentioning
confidence: 99%